Who seeks physiotherapy or exercise treatment for hip and knee osteoarthritis? A cross‐sectional analysis of the English Longitudinal Study of Ageing. (6th February 2019) - Smith, Toby; Collier, Tom S.; Smith, Benjamin; Mansfield, Michael
Abstract: Objectives: To determine the characteristics of individuals with hip and/or knee osteoarthritis who are recommended to seek physiotherapy or exercise treatment, and to explore which people are more or less likely to follow such recommendations. Methods: All data were obtained from Wave 4 of the English Longitudinal Study of Ageing (ELSA) cohort (2008‐2009), a prospectively collected community‐based dataset. Eligibility was justified by a patient‐reported diagnosis of hip and/or knee osteoarthritis with a visual analog scale (VAS) pain score of 1 or above. Data were collected from a self‐completed questionnaire and nurse assessment visit. Prevalence of being recommended to physiotherapy or exercise (or not) and then the actioning of this recommendation (or not) were calculated and presented as 95% confidence intervals (CI). Data on characteristics of those recommended (or not) were explored using univariate analyses and then a forward selection logistic regression model. Results: In total, 1262 and 1877 individuals with hip and/or knee osteoarthritis pain were analyzed. This included 41% (95% CI: 0.38‐0.44) who had been recommended to seek physiotherapy or exercise treatment. Subsequently, 83% of those recommended sought these treatments. Individuals who presented with isolated knee pain, those who reported "fair" self‐reported general health and were younger had a greater chance of being recommended for physiotherapy or exercise treatment, respectively ( P ≤ 0.02). Conclusion: Encouragement should be given to formal and informal care providers of older people to highlight this inequality. This may then improve current and future access to evidence‐based treatments for this population.